Peran Mahasiswa Kuliah Kerja Nyata (KKN) dalam Pembuatan QRIS dan Google Maps pada UMKM Desa Telaga Jernih Kabupaten Langkat - Ihsan Rahmadi; Muhammad Nabil Alifah; Syazwina Dinda Damara Rais; Putri Amanda Fadila; M Amar Adly (BADAN PENERBIT STIEPARI PRESS, 2025)
Activities Kuliah Kerja Nyata (KKN) in Telaga Jernih Village, Secanggang District, Langkat Regency, focused on empowering Usaha Mikro dan Menengah (UMKM) through digital technology. UMKM play a crucial role in driving local economic growth, yet many remain limited in implementing digital strategies. Therefore, outreach was conducted on the use of the Quick Response Code Indonesian Standard (QRIS) as a means of cashless transactions and the use of Google Maps as a business promotion medium. The implementation method involved initial observation to identify needs, followed by door-to-door outreach to UMKM. The results showed that UMKM responded positively to the information provided. They understood that the use of QRIS could facilitate more practical, secure, and transparent transactions, as well as assist with business financial management. Meanwhile, the use of Google Maps was deemed effective in increasing business visibility, expanding market reach, and building consumer trust through address features, photos, and customer reviews. The implementation of the activities ran smoothly without significant obstacles, supported by adequate devices and internet access. Overall, this KKN activity succeeded in increasing the knowledge and awareness of UMKM actors regarding the importance of business digitalization, so it is hoped that it can strengthen competitiveness and support local economic growth in Telaga Jernih Village.